(untitled) (Baghdad Science Journal, 2025)
The effects of gamma irradiation on the structure of ZnS films , which preparing by flash evaporation method, are studied using XRD. Two peaks of (111), (220) orientations are appeared in X ray chart indicating the cubic phase of the films .The lattice parameter, grain size, average internal stress, microstrain, dislocation density and degree of preferred orientation in the film are calculated and correlated with gamma irradiation.